A new predictive factor VGF based on IHC experiments, gene pathways and molecular functional groups for tumor immune microenvironment and prognosis of adrenocortical carcinoma - Chi, Junpeng; Lou, Keyuan; Zhang, Jiankun; Wu, Jitao; Cui, Yuanshan (Frontiers in Immunology, 2025)
BackgroundAdrenocortical carcinoma (ACC) is a rare and aggressive malignancy with a poor prognosis, and its clinical management remains a significant challenge due to the high recurrence rates and limited treatment options. Despite advances in understanding the molecular mechanisms underlying ACC, no reliable biomarkers have been validated for routine clinical use.MethodsWe analyzed RNA sequencing data from The Cancer Genome Atlas (TCGA) database (n=79) and Genotype Tissue Expression (GTEx) database (n=128) to investigate the expression of VGF in ACC and normal adrenal tissues. Gene expression levels of VGF were quantified and correlated with clinicopathological features and survival outcomes. Statistical methods included Cox proportional hazards models and Kaplan-Meier analysis, while Gene Set Enrichment Analysis (GSEA) was utilized to identify relevant biological pathways associated with VGF expression. Clinical data from 7 ACC patients from YANTAI YUHUANGDING Hospital were also analyzed. The expression of VGF in ACC and normal adrenal gland tissue was further validated through IHC experiments.ResultsOur results demonstrate that VGF expression is elevated in ACC tissues compared to normal adrenal tissues and is significantly associated with advanced disease stages, lymph node involvement, metastasis and poor overall survival. VGF levels also correlate with immune cell infiltration, including Th2 cells, T helper cells, and Neutrophils. Importantly, our study establishes VGF as a potential prognostic biomarker for ACC and highlights its role in tumor progression and immune modulation. Additionally, GSEA analysis suggests that VGF is involved in cytokine receptor interaction and the P13K-Akt signaling pathway, possibly relating to tumor immunity.ConclusionsVGF could serve as a valuable marker for patient stratification, monitoring disease progression, and predicting responses to immunotherapies. Future studies should focus on investigating circulating VGF levels as a non-invasive biomarker for ACC to improve clinical management and treatment outcomes.